Comparison between a fitness tracker (EquimetreTM) and standard base-apex electrocardiography in dromedary camels - Al Khamis, Taleb; Shawaf, Turke; Almubarak, Adel; Al-Ali, Mohammed Ali (Frontiers in Veterinary Science, 2023)
Background Personalized healthcare technology has grown explosively through the use of portable and smart monitoring devices for diagnosis. The objective of this study was to determine the practicality and usability of the EquimetreTM fitness tracker on camels in comparison to the standard base-apex system in normal and clinical cases. Methods Five apparently healthy adult camels, five clinical adult cases and two clinical calves were enrolled in this study. The camels were equipped with two monitoring systems: EquimetreTM and a standard base-apex electrocardiogarphy. Each tracing was evaluated for the normal ECG variable's measure, including heart rate beats per min, P-R, QRS, R-R, Q-T, S-T intervals, and P-R and S-T segments in seconds. The amplitudes for P, Q, R, S, and T-peaks were evaluated in millivolts. Results EquimetreTM showed stability on ECG tracing with less movement artifacts compared with the standard base-apex system. Different polarities were observed for the P-waves and T-waves between the standard base-apex system and EquimetreTM. Both devices showed perfect agreement for heart rate (ICC = 1.00, P ≥ 0.0001, 95% = 1.00–1.00) in healthy and clinical adults. A good correlation was observed for the R-R interval between the devices in healthy and clinical adults. A moderate correlation was observed between the devices for Q-peak in clinical adults, with no correlation in clinical calves. Conclusions This study demonstrated acceptable ECG measurements between the standard base-apex and EquimetreTM device. This suggests that EquimetreTM could be a useful device in camels for initial electrocardiographic examinations in remote areas such as deserts.